Social media marketing for dummies - Singh, Shiv (Wiley, 2012)
Get the last word on the most up-to-date social media marketing techniques</​b> If you're not tweeting, Facebooking, or blogging by now, your business is getting left behind. Social media marketing is a highly effective way to engage with your customers. It's an easy, inexpensive way to enlarge your audience, add customers, and build your business. This guide provides an indispensable resource for small businesses and start-ups looking for low-cost online marketing strategies, as well as for marketers in larger companies who want to be more involved with social media. Learn which social media sites best fit your business and how to take full advantage of them.